Youth Intimacy on Tumblr: A Pilot Study. (August 2015) - Hart, Matt
I examine young people's intimate relationships formed on Tumblr. Research has extensively documented how and why adults utilize online dating services to articulate relationships online; however, scholars of this phenomenon have largely overlooked the lived experiences of young people. This article presents the initial findings of a qualitative pilot study in which 10 young male and female Tumblr users participated in hour-long, in-depth, semi-structured, synchronous online interviews via Skype. The initial findings generated by the pilot study suggest that young people are engaging online technologies to practice intimacy and sociality in diverse ways. Responses suggest that young people conceptualize Tumblr as being distinct from existing social network sites (SNS) as a result of its perceived affordances. Iconclude that the ways in which young people engage and date and socialize on Tumblr suggest a rethinking of established contemporary notions of intimacy and community in the digital era.